Immunohistochemical characterization of novel monoclonal antibodies against the N-terminus of amyloid β-peptide. (5th July 2013) - Verwey, Nicolaas A.; Hoozemans, Jeroen J.M.; Korth, Carsten; van Royen, Marloes R.; Prikulis, Ingrid; Wouters, Dorine; Twaalfhoven, Harry A.M.; van Haastert, Elise S.; Schenk, Dale; Scheltens, Philip; Rozemuller, Annemieke J.M.; Blankenstein, Marinus A.; et al.
Abstract: Amyloid β-peptide (Aβ) is a key molecule in Alzheimer's disease (AD). Reliable immunohistochemical (IHC) methods to detect Aβ and Aβ-associated factors (AAF) in brain specimens are needed to determine their role in AD pathophysiology. Formic acid (FA) pre-treatment, which is generally used to enable efficient detection of Aβ with IHC, induces structural modifications within the Aβ, as well as in AAF. Consequently, interpretation of double IHC stainings becomes difficult. Therefore, serial stainings of two newly produced monoclonal antibodies (mAbs) VU-17 and IC16 and two other mAbs (6E10 and 3D6) were performed with four different pre-treatments (no pre-treatment, Tris/EDTA, citrate and FA) and additionally six IHC characteristics were scored: diffuse/compact/classic plaques, arteries with cerebral Aβ angiopathy, dyshoric angiopathy, capillaries with dyshoric angiopathy. Subsequently, these stainings were compared with IHC procedures, which are frequently used in a diagnostic setting, employing mAbs 4G8 and 6F/3D with FA pre-treatment. IHC Aβ patterns obtained with VU-17 and, IC16 and 3D6 without the use of FA pre-treatment were comparable to those obtained with 4G8 and 6F/3D upon FA pre-treatment. Omission of FA pre-treatment gives the advantage to allow double IHC stainings, detecting both Aβ and AAF that otherwise would have been structural modificated upon FA pre-treatment.